2015
DOI: 10.1111/jace.13398
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Phase Structure of Ru–Ti–O Complex Oxide Electrocatalyst

Abstract: Phase stability of (Ru 1x ,Ti x )O 2 solid solution was investigated via materials computation and X-ray diffraction phase analyses. The unit cell volume of (Ru 1x ,Ti x )O 2 was found not increasing monotonously with the fraction of TiO 2 , making the volume-composition relationship no longer suitable for the quantitative phase analysis. A monotonous nonlinear c/a-x relation obtained from the ab initio density functional theory (DFT) computation was proved critical to achieving accurate phase analysis results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…Structural data from Rietveld fitting for the RuO 2 sample indicated the presence of a single phase with lattice parameters a = b = 4.490 Å and c = 3.086 Å. This structure was in good agreement with the calculated parameters determined by DFT, a = b = 4.487 Å and c = 3.108 Å, and those reported in the literature. The Ru 1– x Ti x O 2 ( x = 0, 12.5, 20, and 50 at. %) samples showed the presence of two phases, one of which was in a lower proportion of 2–14% (Table S3).…”
Section: Resultssupporting
confidence: 82%
“…Structural data from Rietveld fitting for the RuO 2 sample indicated the presence of a single phase with lattice parameters a = b = 4.490 Å and c = 3.086 Å. This structure was in good agreement with the calculated parameters determined by DFT, a = b = 4.487 Å and c = 3.108 Å, and those reported in the literature. The Ru 1– x Ti x O 2 ( x = 0, 12.5, 20, and 50 at. %) samples showed the presence of two phases, one of which was in a lower proportion of 2–14% (Table S3).…”
Section: Resultssupporting
confidence: 82%
“…The mixed oxides were prepared by thermal decomposition of precursors mixtures, exactly reproducing the preparation used by Bandi et al in their works. , It is established that mixed Ru–Sn oxides monophasic solid solutions can be prepared over the whole composition range . In contrast, the crystal structure of mixed Ru–Ti oxide is the subject of controversy. , Several studies on Ru–Ti oxide prepared via thermal decomposition (the same procedure used in our work) postulate the formation of a (meta)­stable solid solution for a large compositional window. , In contrast, oxides prepared via sol–gel routes tend to result in two separate phases . Our XRD results (Figure S11) showed the formation of a monophasic solid solution for Ru–Sn oxides and for Ru:Ti of 50:50 (at:at), while a biphasic structure was formed increasing the Ti content (Ru:Ti of 25:75).…”
Section: Resultsmentioning
confidence: 58%
“…37 In contrast, the crystal structure of mixed Ru−Ti oxide is the subject of controversy. 38,39 Several studies on Ru−Ti oxide prepared via thermal decomposition (the same procedure used in our work) postulate the formation of a (meta)stable solid solution for a large compositional window. 38,40 In contrast, oxides prepared via sol−gel routes tend to result in two separate phases.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the calculated critical composition point of 0.538 is slightly inconsistent with the two‐phase dissolution deviation. Wang et al have studied the Ru 1− x Ti x O 2 solid solution by means of experiment and theoretical calculation. They modified the temperature‐dependent interaction parameters to describe the larger critical component point, and found that the excessive critical temperature (3939 K) leads to the narrow range of single‐phase solid solution in the phase diagram.…”
Section: Introductionmentioning
confidence: 99%